Implementasi Smart Irrigation System berbasis Komunikasi ESP-NOW dan Alternate Wetting and Drying (AWD) di Sawah Area Sumatera Selatan - Ayu Kirani Azzahra; Junita Insyirah Nur Huwaida; Menik Ariani; Assaidah Adnan (Universitas Andalas, 2025)
A Smart Irrigation System has been designed and implemented utilizing the Alternate Wetting and Drying (AWD) method and ultrasonic sensors to assist farmers in monitoring and maintaining the water level in rice fields to ensure it is at the level required by rice plants. This system sends a WhatsApp notification if the water level exceeds 15 cm above ground level. The ultrasonic sensor calibration results show an R2 value of 1.0, indicating that the sensor has met the linearity standard. Laboratory testing was conducted by varying three water conditions: below ground level 15 cm; exactly 15 cm above ground level; or more than 15 cm from ground level. Communication between the sender and receiver uses the ESP-NOW protocol. The results show that the sender successfully instructs the solenoid valve to open the tap when the water level is below 15 cm so that water can flow and close it again when the water level reaches 15 cm. There is a 7-second delay when the solenoid opens due to the Normally Closed (NC) type which requires high voltage and current. When the water level exceeds 15 cm above ground level, the system successfully sends a notification to the farmer (user) to drain the water from the field. Field tests in rice fields showed that the water level measurement of 25 cm was in accordance with the reference measuring instrument and successfully provided an accurate warning for farmers to turn on the pump so that the water level returned to the ideal status.